A Cartography of Figurative Knowledge (KULT_online, 2009)
From the German publishing house Wissenschaftliche Buchgesellschaft comes the second printing in just over a year of the Wörterbuch Philosophischer Metaphern. Edited by philosopher Ralf Konersmann, the dictionary of philosophical metaphors is broken into 40 chapters by notable scholars, who delve into one or two notable metaphors. In each of these analyses, the authors employ the philosophical canon to reveal metaphorical functions, and trace (scientific) historical meaning development through to the present-day. Bringing together approaches from rhetoric, aesthetics, and the philosophy of science, this volume offers many jumping-off points for further research in cultural studies and philosophy. It is also accessible to the general audience interested in linguistics.